English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

5
Sigma (2^-k - 2^-k - 1) =
k=1

2006-10-26 15:18:29 · 3 answers · asked by Olivia 4 in Science & Mathematics Mathematics

3 answers

5
∑(2^-k - 2^-(k+1)) =
1

5
∑2^-k( 1 - 2^-1)) =
1

... 5
½∑2^-k =
... 1

½ (2^-1 + 2^-2 + 2^-3 + 2^-4 + 2^-5) =

¼ (1 - 1/16) Sum the first 5 terms of GP with a = ½, r = ½ and n = 5)

= 15/64

2006-10-26 15:44:57 · answer #1 · answered by Wal C 6 · 1 0

You must have a mistake in your equation. The two 2^-k terms cancel out leaving -1, which is the sum independent of the number of k terms added.

2006-10-26 15:21:35 · answer #2 · answered by gp4rts 7 · 0 0

Looks like the 2^-k - s^-k cancel out each time, so I'd just add -1 5 times, and get -5.

2006-10-26 15:23:35 · answer #3 · answered by Anonymous · 0 0

fedest.com, questions and answers